Studi Kesesuaian dan Daya Tarik Wisata di Pantai Bosur Tapanuli Tengah Ditinjau dari Aspek Biofisik (Study of Suitability and Appeal of Tourism in Bosur Beach Central Tapanuli from Biophysical Aspect) - Brawijaya Hutabarat; Miswar Budi Mulya; Zulham Apandy (AQUACOASTMARINE, 2016)
Bosur beach located in Central Tapanuli where it has great potential to be developed as a tourist beach. This study aimed to analyze the suitability of coastal tourism on biophysical and also the level carrying capacity Bosur beach as a tourist attraction and to know the perception of tourist. The study was held on August 2015. Analyze of the data used purposive sampling method. This research used suitability analysis method and carrying capacity of the region, and the perception of tourists to find out the beauty value and comfort value. The results of the suitability analyzes for beach tourism is classified very appropiate (S1), for category of swimming is classified appropiate criteria (S2) and a category boating and Banana boat is classified appropriate criteria (S2). Carrying capacity of the Bosur beach can accomodate 884 tourists every day. Perception of tourists about beauty value of Bosur beach is 49%, and the comfort value of Bosur beach is 51%.Keywords : Bosur beach, Carrying capacity of the region, Land suitability assessment,The perception of tourists, Tourist attraction